2022
DOI: 10.3390/su14031054
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Insight through a Keynesian Theory Approach to Investigate the Economic Impact of the COVID-19 Pandemic in Pakistan

Abstract: Beyond the immediate impositions of dealing with COVID-19, this disease represents a severe and significant challenge confronting Pakistan’s economy. The study’s objective was to evaluate the coronavirus epidemic’s effect on Pakistan’s economy and measures devised to mitigate the damage done by this disease. The study research design used the elementary concept of Keynesian theory comprising of the mapping of systematic behavior of the COVID-19 pandemic. Issues were formally underpinned, described, and visuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 66 publications
1
36
0
Order By: Relevance
“…As a result, it disturbed the economic and social cycle of the world economy and created instability in the many sectors of the economy (Abbass et al 2022c ). Abbass et al ( 2022d ) used the Keynesian theory and identified that the COVID-19 explosion has significantly shaken the domestic and global economy.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it disturbed the economic and social cycle of the world economy and created instability in the many sectors of the economy (Abbass et al 2022c ). Abbass et al ( 2022d ) used the Keynesian theory and identified that the COVID-19 explosion has significantly shaken the domestic and global economy.…”
Section: Introductionmentioning
confidence: 99%
“…The provincial governments formed their own sets of legislation, namely Infectious Disease Prevention and Control Ordinances under the previous laws for prevention of epidemics known as Public Health (Emergency Provisions) Ordinance 1994 ( 96 ). Furthermore, the federal government of Pakistan, with the collaboration of international organizations, including WHO, took necessary precautions and different measures against the COVID-19 pandemic, which not only ensured containment of disease spread risk but also fulfilled its responsibility as a state toward its population's safety ( 97 ). The pandemic has also exposed the limitations and institutional weaknesses within the criminal justice system, underscoring the need for implementing timely and adequate response strategies to emerging issues ( 98 ).…”
Section: A Discussion On Comparison Of Law Policy and Governance For ...mentioning
confidence: 99%
“…One for invitation, second for rapport development and briefing for concept, and third for data elicitation. The data is elicited individually from all experts on ij part of matrix type questionnaire which was subsequently aggregated by majority rule (Li et al 2019a , b ; Qazi et al 2019 ; Ahmad et al 2022 ; Abbass et al 2022e ; Basit et al 2021 ). The experts were involved at three stages: first for verification of identified determinants, second for data collection, and third for model confirmation (Vasanthakumar et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%